THE ROLE OF E-HEALTH TECHNOLOGIES IN IMPROVING HEALTHCARE ACCESSIBILITY AND EQUITY FOR PEOPLE WITH DISABILITIES - Aneta Rasińska; Justyna Jachimczak; Justyna Matusik; Mateusz Kopczyński; Piotr Rzyczniok; Paulina Bala (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: E-health technologies have the potential to transform healthcare accessibility and quality for people with disabilities. However, multiple barriers limit their effective use and exacerbate health disparities. This narrative review aims to synthesize current knowledge on e-health interventions designed for disabled populations, identify challenges and best practices, and explore future perspectives to enhance health equity.Review Methods: A comprehensive narrative review was conducted using peer-reviewed articles, case studies, and official reports published primarily between 2013 and 2022. Searches were performed across databases such as PubMed, Scopus, and Web of Science, focusing on keywords related to e-health, disabilities, accessibility, and health equity. Literature was qualitatively analyzed to identify key themes around accessibility barriers, successful e-health implementations, strategic interventions, and emerging technologies.State of Knowledge: Findings reveal that accessible design, digital literacy support, inclusive policies, community engagement, and robust privacy measures are critical for effective e-health adoption among people with disabilities. Case studies demonstrate improvements in healthcare access and outcomes when these factors are addressed. Emerging technologies like artificial intelligence, the Internet of Things, and virtual reality offer promising avenues for personalized and adaptive care. Nonetheless, economic, technological, and socio-cultural challenges persist, necessitating coordinated efforts across disciplines.Conclusion: E-health holds significant promise to reduce health disparities for people with disabilities. Realizing this potential requires integrating universal design principles, enhancing digital inclusion, fostering policy reforms, and maintaining ethical vigilance. Collaborative, inclusive innovation can ensure that future digital health solutions contribute meaningfully to equitable healthcare and improved wellbeing for all.